1910 Md. Laws 521 - (:unkn) unknown (My University, 1910)
§ 16c. That it shall be unlawful for any person to hunt, pursue or kill any of the birds or animals named in Section 12, 13, 14 and 14A of this Act, or any insectivorous birds (excepting English sparrows), in Allegany County on Sunday, or on election days, and it shall be prima facie evidence of a violation of this Act if any person is found in the fields or woods with on a gun on Sunday or on election days, or to hunt or kill in any trap or destroy any of the birds . . .
Keywords: HUNTING REGULATION